The Effect of Inventory Management, Executive Compensation, Intelectual Capital and Leverage on Company Performance: PENGARUH MANAJEMEN PERSEDIAAN, KOMPENSASI EKSEKUTIF, INTELLECTUAL CAPITAL DAN LEVERAGE TERHADAP KINERJA PERUSAHAAN - Zulaecha, Hesty Erviani (Fundamental Management Journal, 2017)
This study aims to determine the effect of inventory management, intellectual capital, executive compensation and leverage on the performance of companies in manufacturing companies listed on the Indonesia Stock Exchange with Automotive subsektor. The number of samples of this study are 14 companies in 5 periods, namely from 2011-2015. The research method used is multiple linear regression method using SPSS version 24 program. The result of this research stated that inventory management and leverage have no significant effect to company performance, while executive compensation and Intellectual Capital have positive and significant influence to company performance.Keywords: Inventory Management, Executive Compensation, Intellectual Capital, Leverage, Company Performance